Віддзеркалення геополітичних реалій 1941–1943 рр. у політичній карикатурі окупаційної преси Чернігівської та Сумської областей - Горох, М.В. (Сіверщина в історії України, 2021)
Стаття присвячена з’ясуванню ролі і місця політичної карикатури у формуванні інформаційного простору на території Чернігівської та Сумської областей у роки Другої світової війни. Аналіз візуальних образів, розміщених на сторінках окупаційної преси,
сприяє розкриттю концепції ідеологічних маніпуляцій нацистського режиму, дозволяє оцінити їхній вплив на процес формування архетипів сприйняття як на населення окупованої України, так і на
сучасників. Особлива увага приділена послідовності появи карикатур, співставлення їхнього змісту з подіями на фронтах Другої світової війни. Проаналізовано видання, в яких друкувалися
рисунки, встановлена динаміка появи та тематика зображень. The article is devoted to the clarification of the political caricature’s role
and position in the forming of the informational space on the Chernihiv and
Sumy region territory during World War II. In 1941–1943 the occupation authorities
published 15 newspapers in Chernihiv, Nizhyn, Pryluky, Snovsk, Ostry,
Semenivka, Novhorod-Siverskyi, Sumy, Romny, Konotop, Krolevets, Okhtyrka,
Shostka, Putivl. We find caricatures in 219 issues of 813. Most of the images
are in the «Ukrainske Polissia» (53 issues), «Sumskyi visnyk» (47), «Nizhynski
visti» (30), «Holos Okhtyrshchyny» (29) and «Visti Pryluchchyny» (23). Newspapers
promptly introduced readers to the front lines, orders and announcements
of the occupation administration and orders of the German command.
The analysis found that the publication of the occupation media had a clear
anti-Soviet and anti-Semitic orientation. Some caricatures were used for purely
tactical reasons, directing the incitement of international enmity. The rest images
orientation was more distant, strategic objectives, which was to discredit
the Soviet leadership as reckless and criminal. The occupation press ridiculed
the anti-Hitler coalition figures (Stalin, Roosevelt, Churchill), the inability of
the Allies to withstand the German military units and secure the admission of
the Lend-Lease program. Based on the moral and psychological and ideological
stereotypes of marginalized group Ukrainian society Nazi propaganda exploited
the worst traits and feelings, directing them to support the awful terror.
The key events on the fronts of the World War II and relations between the
allies were reflected, albeit belatedly, through the cartoons in the pages of the occupational press. The analysis of the visual images on the pages of the occupational
press helps to reveal the concept of ideological manipulations of the Nazi
regime. It also helps to evaluate their influence on the forming of the perception
archetypes of both people of occupied Ukraine and people who live nowadays.